2002
DOI: 10.1038/sj.mp.4001144
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic model of comorbid Tourette's syndrome and obsessive-compulsive disorder circuitry

Abstract: The tic disorder Tourette's Syndrome (TS) and obsessive-compulsive disorder (OCD) are comorbid behavioral disorders, suggesting a shared but still unknown neuronal basis. To 'circuit-test' such behaviors, we previously engineered transgenic mice expressing a neuropotentiating protein (cholera toxin A1 subunit) within a cortical-limbic subset of dopamine D1-receptor expressing (D1+) neurons known to trigger glutamatergic excitation of orbitofrontal, sensorimotor, limbic and efferent striatal circuits thought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 47 publications
5
118
0
Order By: Relevance
“…In an experimental study, Nordstrom et al 25 found that the hypoactivity of glutamatergic efferent cortical-limbic pathways leads to ADHD.…”
Section: Studies N=276mentioning
confidence: 99%
See 1 more Smart Citation
“…In an experimental study, Nordstrom et al 25 found that the hypoactivity of glutamatergic efferent cortical-limbic pathways leads to ADHD.…”
Section: Studies N=276mentioning
confidence: 99%
“…25,34 Some hormones seem to play a role in the cooccurrence of TS+OCD. The onset and recurrence of TS have been associated with significant emotional contexts.…”
Section: Ocd and Other Anxiety Disordersmentioning
confidence: 99%
“…15 The majority of studies conducted to date have focused on genes important in the serotonin and dopaminergic neurotransmitter systems due to the efficacy of serotonin reuptake inhibitors (SRIs) and dopamine antagonists in the treatment of OCD patients. [16][17][18] In summary, even though the genetic transmission of OCD is indisputable, the mode of transmission and the genes involved are still unknown. A major difficulty in genetic studies of complex disorders such as OCD has been sample heterogeneity.…”
Section: Brief Overview Of Genetic Studies Of Ocdmentioning
confidence: 99%
“…This is presumed to increase their firing rate in a way that may resemble the hyperactive limbic cortical areas seen in functional imaging of OCD patients; indeed, these transgenic mice are described as engaging in perseverative behaviors that mimic some aspects of OCD and Tourette's syndrome. 78,79 MK-801, a noncompetitive use-dependent antagonist of the NMDA glutamate receptor that may indirectly increase presynaptic glutamate release, 80 has been shown to worsen these perseverative behaviors, and to induce an additional category of "limbic seizure-like" stereotypies. 81 Interestingly, 2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo(f)quinoxaline (NBQX), an antagonist of AMPA-type glutamate receptors, does not affect baseline OCD-like behaviors in these mice or their exacerbation by MK-801, but does reduce the "seizure-like" stereotypies.…”
Section: Preclinical Evidence Suggesting Increased Glutamate Activitymentioning
confidence: 99%